2021
DOI: 10.21608/ejhm.2021.144902
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guided Serratus Anterior Plane Block versus Thoracic Epidural Analgesia in Breast Surgery

Abstract: Background: Breast Surgery is becoming more and more common. Patients are often middle-aged women and with high public awareness around issues of breast cancer. The numbers are increasing. Breast surgery is an exceedingly common procedure and associated with an increased incidence of acute and chronic pain. Regional anesthesia techniques may improve postoperative analgesia for patients undergoing breast surgery. Objective: To assess the efficacy and safety of ultrasound-guided serratus anterior plane block (SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…All included studies report 24-h postoperative VAS [ 10 , 11 , 12 , 17 , 19 , 20 ]. There was significant heterogeneity among the trials ( χ 2 = 361.54, P < 0.00001, I 2 = 99%).…”
Section: R Esultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All included studies report 24-h postoperative VAS [ 10 , 11 , 12 , 17 , 19 , 20 ]. There was significant heterogeneity among the trials ( χ 2 = 361.54, P < 0.00001, I 2 = 99%).…”
Section: R Esultsmentioning
confidence: 99%
“…Five studies reported the VAS score on 12 h postoperative [ 11 , 12 , 17 , 19 , 20 ]. Heterogeneity was found in the pooled results of the trials ( χ 2 = 170.56, P < 0.00001, I 2 = 98%) and significantly no difference in pain on 12 h postoperative in both the groups (MD = -0.06, Z = 0.15, P = 0.88) [ Figure 4b ].…”
Section: R Esultsmentioning
confidence: 99%
See 3 more Smart Citations